Imersões isométricas em grupos de Lie nilpotentes e solúveis - Melo, Marcos Ferreira de (2008)
In this paper, we prove theorems establishing sufficient conditions to existence for isometric immersions with prescribed extrinsic curvature in two-step nilpotent Lie groups and solvmanifolds. We obtain a generalization of the Fundamental Theorem of Submanifold Theory in Rn and, in particular, we one has immersion results in the generally Heisenberg type groups and Damek-Ricci spaces.